Kekerasan dalam Rumah Tangga - Hidayani Syam; Syahlu Andalusia Monrick; Silva Khairani (Mandub : Jurnal Politik, Sosial, Hukum dan Humaniora, 2025)
Domestic violence (DV) is a form of human rights violation that often occurs but is still widely unreported. This study aims to examine the forms of domestic violence, the factors that cause it, and its impact on victims, especially women and children. The method used is the library research method. The results of the study indicate that physical, psychological, sexual, and economic violence are the most common forms of domestic violence. The dominant factors causing domestic violence include patriarchy, economic dependence, alcohol abuse, and weak law enforcement. The impacts are not only physical, but also psychological and long-term social. This study recommends increasing public education, strengthening victim protection institutions, and stricter law enforcement against perpetrators of domestic violence. Handling domestic violence holistically is the key to creating a safe and healthy family environment.